Review of the Australian Cyllodini (Coleoptera: Nitidulidae: Nitidulinae), with descriptions of new taxa, and notes on the genus Macleayania (Nitidulini) - Lawrence, John F.; Kirejtshuk, Alexander G. (Zootaxa, 2019)
The genera of the nitiduline tribe Cyllodini occurring in Australia are reviewed and a key is provided for their separation. Each genus is discussed, with an emphasis on the Australian fauna, and an hypothesis is given concerning the source of the introduced Camptodes species and its connection with the program for biological control of Opuntia cacti. The specimens identified by Kirejtshuk (2003) as Macleayania amphotiformis (Reitter, 1880b) were found to represent two widely overlapping species later named by Olliff (1886) in the trogossitid genus Ancyrona. The following new genus and species are included: Cyllopallodes, gen. nov., Gymnocychramus bicolor, sp. nov., Pallodes nigroapicalis, sp. nov. The following new combinations and synonymies are also included: Coxollodes loriai (Grouvelle, 1906) (Pallodes) (= Pallodes opacus Grouvelle, 1906, syn. nov.); Cyllodes ruficeps (Reitter, 1880a) (Strongylus) (= Pseudocamptodes blackburni Grouvelle, 1902, syn. nov.; Pseudocamptodes fulviceps Grouvelle, 1906, syn. nov.); Cyllopallodes limbicollis (Reitter, 1880b) (Pallodes), comb. nov.; Pallodes beccarii Grouvelle, 1906 (= Pallodes gestroi Grouvelle, 1906, syn. nov.); Macleayania amphotiformis (Reitter, 1880b) (= Ancyrona amica Olliff, 1886, syn. nov.); Macleayania vesca (Olliff, 1886) (Ancyrona) comb. nov. The lectotypes of Camptodes humeralis (Brullé, 1842), Coxollodes loriai (Grouvelle, 1906), C. opacus (Grouvelle, 1906), Cyllodes fulvipes (Grouvelle, 1906), Pallodes beccarii Grouvelle, 1906, P. gestroi Grouvelle, 1906, and P. misellus Grouvelle, 1906 are designated. Information on and syntype information from Macleayania amica (Olliff, 1886), M. vesca (Olliff, 1886), Cyllodes blackburni (Grouvelle, 1906) and C. rufipes (Reitter, 1880a) are given.